Eriobotrya japonica (Loquat) juice production parameters and their effect on sensory attributes and phenolic content - Dimassi, Ossama; Hariri, Alberta; Akiki, Raymond; Rached, Mohammad; El Hajj, Fatima (International Journal of Environment, Agriculture and Biotechnology, 2020)
The aim of this study is to assess the juice production potential of a highly perishable fruit, namely loquat and the effect of basic thermal and chemical treatment on the sensory attributes and phenolic content. The scarcity of loquat-based products on the market limits its consumption to raw loquat fruit. It is highly perishable and thus quickly loses its postharvest commercial quality. Loquat transformation into juice would increase the pellet of loquat-based products. Loquat fruit to loquat juice conversion value ranged between 1.79, 1.78, 2.41 and 2.39Kg of loquat fruit to produce 1kg of diluted fresh loquat juice, diluted fresh loquat juice with citric acid, pasteurized diluted loquat juice and pasteurized diluted loquat juice with citric acid respectively. The dilution factor was 0.2. All the Sensory attributes; taste, texture, appearance, aroma and overall-acceptance were significantly higher for both un-pasteurized loquat juices when compared with the pasteurized ones. Total Soluble Solids (TSS) values and TSS/Titratable-Acidity of the two pasteurized loquat juices were significantly higher than those which were not, given that water-activity and pH did not differ. TSS was significantly and negatively correlated with all the sensory attributes. Finally yet importantly, the phenolic content of the untreated fresh loquat juice scored significantly the lowest while the phenolic effect of the other juices did not differ significantly from each other. When the phenolic content per100gr TSS where the loquat juice with 1% citric acid scored significantly the highest than all of the other juices which did not differ significantly from each other.